Advances in Communication, Cloud, and Big Data Proceedings of 2nd National Conference on CCB 2016 - Sarma, Hiren Kumar Deva.; Borah, Samarjeet; Dutta, Nitul; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book is an outcome of the second national conference on Communication, Cloud and Big Data (CCB) held during November 10-11, 2016 at Sikkim Manipal Institute of Technology. The nineteen chapters of the book are some of the accepted papers of CCB 2016. These chapters have undergone review process and then subsequent series of improvements. The book contains chapters on various aspects of communication, computation, cloud and big data. Routing in wireless sensor networks, modulation techniques, spectrum hole sensing in cognitive radio networks, antenna design, network security, Quality of Service issues in routing, medium access control protocol for Internet of Things, and TCP performance over different routing protocols used in mobile ad-hoc networks are some of the topics discussed in different chapters of this book which fall under the domain of communication. Moreover, there are chapters in this book discussing topics like applications of geographic informationsystems, use of radar for road safety, image segmentation and digital media processing, web content management system, human computer interaction, and natural language processing in the context of Bodo language. These chapters may fall under broader domain of computation. Issues like robot navigation exploring cloud technology, and application of big data analytics in higher education are also discussed in two different chapters. These chapters fall under the domains of cloud and big data, respectively.
Chapter 1. Survey on Energy Efficient Routing Protocols in Wireless Sensor Networks using Game Theory -- Chapter 2. Design and Analysis of Optimum APSK Modulation Technique -- Chapter 3. Big Data Analytics in the Higher Education: Need of the future. Chapter 4. Land Capability Classification for Agriculture: GIS and Remote Sensing Approach: A Survey -- Chapter 5. Review on Vehicular Radar for Road Safety -- Chapter 6. Landmark Based Robot Navigation: A Paradigm Shift from Onboard Processing to Cloud -- Chapter 7. From Cognitive Psychology to Image Segmentation: A Change of Perspective -- Chapter 8. An Exploration in Perception Based Digital Media Processing: A Psychological Perspective -- Chapter 9. Converting and developing live website into a web content management system -- Chapter 10. A Review on Existing QoS Routing Protocols Based on Link Efficiency and Link Stability -- Chapter 11. A Diamond Shaped Fractal Bow-Tie Antenna for THz Applications -- Chapter 12. A Study on Few Approaches to Counter Security Breaches in MANETs -- Chapter 13. A Survey: EMG Signal Based Controller as Human Computer Interaction -- Chapter 14 [CCB 1622-] IEEE 802.15.4 as the MAC protocol for Internet of Things (IoT) Applications for achieving QoS and Energy Efficiency -- Chapter 15. HMM Based Speaker Gender Recognition for Bodo Language -- Chapter 16. Accurate Drainage Network Extraction From Satellite Imagery -a Survey -- Chapter 17. Survey on Transmission Control Protocol Performance over different Mobile Ad-Hoc Routing Protocols -- Chapter 18 -- Survey on detection and mitigation of Distributed Denial of Service attack in named data networking.
Keywords: Telecommunication; Big data; Computer input-output equipment; Communications Engineering, Networks; Big Data; Input/Output and Data Communications